THE CORRELATION BETWEEN NON-ENGLISH SPEAKING PARENTS’ INVOLVEMENT, STUDENTS’ PERSISTENCE, AND ENGLISH ACHIEVEMENT AMONG EFL HIGH SCHOOL STUDENTS IN INDONESIA - Sinar Bulan; Nike Angraini; Dio Resta Permana (ELP (Journal of English Language Pedagogy), 2026)
This study investigates the correlation between non-English speaking parents’ involvement, students’ persistence, and their English achievement among EFL high school students at SMA Negeri 11 Palembang, Indonesia. The research aimed to determine whether parents’ involvement and students’ persistence significantly influence students’ English achievement. A quantitative correlational design was employed, using two sets of questionnaires to measure parents’ involvement and students’ persistence, along with an English achievement test. The findings revealed no significant correlation between non-English speaking parents’ involvement and students’ English achievement (r = 0.090, p > 0.05). Similarly, no significant relationship was found between students’ persistence and their English achievement (r = 0.815, p > 0.05). These results suggest that factors such as parents’ limited knowledge of English, low self-efficacy, socioeconomic background, and weak parent–school communication may contribute to the absence of significant relationships. The study highlights the need for schools to strengthen parental engagement programs and to foster students’ motivation and self-regulated learning strategies to enhance English achievement.